Kurusıkı Tabancanın Neden Olduğu Ölümcül Kafa Travması - (:unkn) unknown (My University, 2013)
Kurusıkı tabancalar sadece ses ve gaz fişekleri ateşleyen düzeneklerdir. Dış görünümleri ve çıkardıkları ses bakımından gerçek silahlardan ayırt edilmeleri çok güçdür. Bu özellikleriyle toplumda adeta zararsız silah imitasyonları şeklinde algılanırlar. Bu olgu sunumunun amacı, toplumda ölümcül etkileri sıklıkla gözardı edilen kurusıkı tabancaların özellikle yakın mesafeden nörokraniuma yapılan ateşlemelerde pnömatik etkileriyle yaratabilecekleri tehlikeleri vurgulamaktır.

Blank cartridge guns only fire sound and gas cartridges and have metal barriers to prevent firing of solid projectiles. Their design and sound is very similar to real guns. Therefore, blank cartridge handguns are generally considered as harmless imitations of real guns and they are underestimated in their capacity to inflict serious and potentially life threatening injuries. The aim of this report is to highlight the potential risks of life threating injuries of these guns.
Lethal Brain Injury Caused By A Blank Cartridge Pistol
Keywords: Nörolojik Bilimler